Comparison of predicted responses to three types of recurrent selection procedures for the improvement of a maize (Zea mays L.) population - Ajala, S.O.; Ago, C.E.; Olaoye , G. (2009)
A maize population was subjected to three different selection procedures to determine the best methodfor its improvement in a study conducted at Ibadan, Nigeria. Considerable genetic variability existedwithin the population for effective selection for each of the traits considered, using any of theprocedures namely full-sib, half-sib and S1 family selection. Heritability estimates were from moderateto large for most traits. Direct selection for grain yield is expected to result in favourable increases inother traits except that the selected materials will flower earlier. Since increases in plant height due toselection for grain yield is undesirable, it was concluded that the best selection method for yieldimprovement that will increase height, the least would be full-sib family selection.